Systematic review and meta-analyses on the effects of whole-body vibration on bone health - Oluwagbemiga O. DadeMatthews; Philip J. Agostinelli; Frances K. Neal; Seun O. Oladipupo; Rebecca M. Hirschhorn; Alan E. Wilson; JoEllen M. Sefton (Elsevier, 2022)
Objective: To determine whole body vibration influence on human bone density and bone biomarkers. Methods: We identified studies in Medline, Web of Science, Cumulative Index of Nursing and Allied Health, SPORTDiscus, Embase and Cochrane from inception to November 2021. Human randomized controlled trials involving commercially available whole body vibration platforms were included. Outcomes included bone density mean difference and serum concentrations of biomarkers (Procollagen type 1 N-terminal Propeptides, Osteocalcin, Bone specific alkaline phosphatase, and C-terminal Telopeptide of type 1 collagen). Random effects model (Hedges' g effect-size metric and 95% confidence-intervals) compared whole body vibration effect on bone density and bone biomarkers. Moderator analyses assessed health status, age, menopausal status, vibration type, vibration frequency, and study duration influence. Results: Meta-analysis of 30 studies revealed bone density improvement after whole body vibration (Hedges' g = 0.11; p = 0.05; 95% CI = 0.00, 0.22). Whole body vibration improved bone density in healthy (Hedges' g = 0.10; p = 0.01; 95% CI = 0.02, 0.17) and postmenopausal women (Hedges' g = 0.09; p = 0.02; 95% CI = 0.01, 0.18). Bone density also increased following side-alternating whole body vibration intervention (Hedges' g = 0.21; p = 0.02; 95% CI = 0.04, 0.37). Whole body vibration had no significant effect on either bone formation biomarkers (Hedges' g = 0.22; p = 0.01; 95% CI = 0.05, 0.40) or bone resorption biomarkers (Hedges' g = 0.03; p = 0.74; 95% CI = −0.17, 0.23). Conclusion: Whole body vibration may be clinically useful as non-pharmacological/adjunct therapy to mitigate osteoporosis risk in healthy postmenopausal females. Additional studies are needed to determine the underlying mechanisms.